2021
DOI: 10.3390/ijms22062889
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Extracellular Vesicles from Human Epidural Fat-Derived Mesenchymal Stem Cells and Fibroblast Cells

Abstract: Extracellular vesicles (EVs) are generated and secreted by cells into the circulatory system. Stem cell-derived EVs have a therapeutic effect similar to that of stem cells and are considered an alternative method for cell therapy. Accordingly, research on the characteristics of EVs is emerging. EVs were isolated from human epidural fat-derived mesenchymal stem cells (MSCs) and human fibroblast culture media by ultracentrifugation. The characterization of EVs involved the typical evaluation of cluster of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…However, several difficulties have been observed in conducting basic studies with EF-MSCs. To date, EVs have been considered as novel source materials for regenerative studies and clinical relevance [3,[7][8][9]29]. EVs exhibit several advantages for such research, and one of their advantages over MSCs is that they do not consume their donor tissues or cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, several difficulties have been observed in conducting basic studies with EF-MSCs. To date, EVs have been considered as novel source materials for regenerative studies and clinical relevance [3,[7][8][9]29]. EVs exhibit several advantages for such research, and one of their advantages over MSCs is that they do not consume their donor tissues or cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some experiments suggest that MSC-EVs can improve inflammatory diseases by modulating immune function ( 21 ). MSC-EVs can inhibit T and B lymphocyte proliferation and induce Treg cell population, and reduce TNF-α expression and increase IL-10 expression by affecting the maturation of macrophages ( 22 ). A study showed, MSC-EV-miR-146a plays an anti-inflammatory role by reducing the mRNA and protein levels of TNF receptor-associated factor 6 (TRAF6) and IL-1 receptor-associated kinase 1 (IRAK1), inhibiting the phosphorylation of NF-κ B p65 and I κ B α, reducing the expression of pro-inflammatory factors, and increasing the level of IL-10 ( 23 ).…”
Section: Mesenchymal Stem Cells and Extracellular Vesiclesmentioning
confidence: 99%
“…Various studies have shown that EVs harbor specific proteins whose quantities increase in patients with breast cancer, which suggests that they could be potential biomarkers for breast cancer [21,22]. Extracellular vesicles range from 40 to 200 nm in size, are characterized by phospholipid bilayers, and are ubiquitous in nearly all body fluids, including the cerebrospinal fluid, saliva, breast milk, and blood [23,24]. The vesicles are released by diverse cell types through the fusion of the plasma membrane with multivesicular bodies and play a crucial role in regulating cell-to-cell communication [25].…”
Section: Introductionmentioning
confidence: 99%